The Influence of Particle Size Sediment on Macrozoobenthos Abundance in Dumai Waters, Rupat Strait - Endah Wulandari; Rifardi Rifardi; Syafruddin Nasution (Jurnal Natur Indonesia, 2026)
The purpose of this study was to determine the effect of sediment texture on macrozoobenthos abundance in Dumai Waters, Rupat Strait. This study, conducted from February to March 2023, used a survey method. Stations were selected purposively. The method used 4 stations to collect samples, which were then analyzed in the laboratory. Analysis carried out in the laboratory comprises sediment fractionation and particle size analysis, and the identification of species of macrozoobenthos. The results of this study show that sediment texture accounts for 77.9% of the variation in macrozoobenthos abundance, while other environmental factors, including physical and chemical factors, account for the remaining 22.1%. The macrozoobenthos species found were Barbatia sp., Marcia hiantina, Nerita articulata, Hiatula sp., and Clypeomorus sp.